Testicular Histomorphometric Parameters and Spermatogenic Dynamics of Monodelphis americana (Müller, 1776) (Didelphimorphia: Didelphidae) - Martins, Ana Luiza Pereira; Dias, Fernanda Carolina Ribeiro; Rodrigues, Grasielle Avelar Vieira; Oliveira, Elizabeth Lopes; Araújo, Adriele Ribeiro; Avelar, Gleide Fernandes; Matta, Sérgio Luis Pinto (Anatomia, histologia, embryologia, 2025)
ABSTRACT The testes of mammals are responsible for gamete production and the secretion of the sex hormone testosterone. Within the seminiferous tubules, spermatogenesis occurs, where germline cells undergo division and differentiation until the formation of spermatozoa. Meanwhile, in the intertubular compartment, Leydig cells produce and secrete testosterone, a hormone essential for spermatogenesis. Monodelphis americana is a marsupial species endemic to Brazil, commonly known as the three‐striped short‐tailed opossum. The reproductive biology of marsupials remains relatively unexplored despite being a crucial tool for understanding species‐specific reproductive strategies, which can aid in management and conservation efforts. In this study, M. americana exhibited a body weight of 36.7 g, with a gonadosomatic index (GSI) of 0.47%, a tubular somatic index (TSI) of 0.36% and an interstitial somatic index (ISI) of 0.27%. The proportion of seminiferous tubules was 83.16%, indicating a significant investment in sperm production. The mitotic and meiotic indices were 1.87 and 2.64 cells per division, respectively, with an overall spermatogenic yield of 12.68. The intertubular compartment accounted for 16.84% of the testicular parenchyma, of which 13.13% consisted of Leydig cells, with a total count of 22.75 × 106 Leydig cells per testis. The findings suggest that M. americana prioritises spermatogenic parameters over the intertubular compartment, implying that males exhibit a promiscuous reproductive behaviour.